Calprotectin mRNA (MRP8/MRP14) expression in neutrophils of periodontitis patients with type 2 diabetes mellitus - Ahmad Syaify; Marsetyawan HNES; Sudibyo Sudibyo; Suryono Suryono (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Calprotectin, a major cytosolic protein of leukocytes, is detected in neutrophils and monocytes/machrophages. This protein is known to be a marker for several inflammatory diseases including periodontitis. In type 2 diabetes mellitus patients, the severity of periodontitis was strongly thought to be caused by decreasing of leukocytes function such as neutrophils. Previous research found that the calprotectin level in serum of periodontitis patients with type 2 DM is higher than periodontits patients non DM. Purpose: The aim of this study was to determine calprotectin mRNA (MRP8/MRP14) expression in human neutrophils of periodontitis patients with type 2 diabetes mellitus. Methods: Neutrophils were isolated from the peripheral blood of periodontitis patients with uncontrolled type 2 DM, controlled type 2 DM, and non DM. The expression of calprotectin mRNA (MRP8 and MRP14) were detected by RTPCR. Result: The result showed that the value of mRNA calprotectin expression in DM patients were higher than non DM, and the highest expression was on the uncontrolled type 2 DM. Conclusion: The basal level of calprotectin mRNA MRP8/MRP14 expression increased in neutrophil of periodontitis patient with type 2 DM compared non diabetic subjects. It was suggested that high basal level of calprotectin mRNA has a role in the regulation of periodontitis severity with diabetes mellitus patients.